Blood pressure response to out-patient drug treatment of hypertension in 1973 - 1993 at Korle-Bu Teaching Hospital, Accra, Ghana - Adukwei Hesse, I.F. (West African Journal of Medicine, 2003)
A retrospective audit of the first twelve months of out patient drug treatment of hypertension at the Korle-Bu Teaching Hospital during the period 1973 - 1993 is reported. A previous study had shown that at least 7 drug regimes were used to treat hypertension at Korle-Bu during the period. The aim of the present study was to compare the effect and efficacy of these antihypertensive drug treatment regimes on blood pressure during the first 12 months of treatment. Result of 155 (47%) case notes, which met the inclusion criteria, are presented. One month of drug treatment of hypertension significantly reduced systolic and diastolic blood pressure by 21.4 ± 30.5 (p<0.001) and 13.8 ± 16.5 (p<0.001)mmHg, respectively. This reduction in blood pressure was maintained to the 12th month. At 12 months, systolic and diastolic blood pressures were unchanged in 19% and 28% of patients, respectively, indicating no response to drug treatment. Recommended target blood pressure of ≤ 140/90mm Hg was achieved in only 25.6% of all patients. All drug treatment regimes significantly reduced blood pressure to a similar extent so that any differences were not statistically significant. However, the efficacy of the drug regimes differed significantly (p=0.02). It was greatest in patients treated with monotherapy with either diuretic or reserpine, intermediate with two drug combinations and least with 3 or 4 drugs. The data showed that diuretics were marginally better than reserpine as first line monotherapy. Furthermore, any diuretic based 2-drug regime was equally efficacious although a beta-blocker or methyldopa as second drug seemed favoured by the data. The addition of a third or fourth drug was counter productive as the increased number of drugs did not decrease blood pressure significantly.
Keywords: African; Antihypertensive drugs; Blood pressure treatment; Ghanaian; Hypertension